PROMOTING FOREIGN LANGUAGE LEARNERS’ WRITING: COMPARING THE IMPACT OF ORAL CONFERENCING AND COLLABORATIVE WRITING - Mania Nosratinia; Niousha Nikpanjeh (University of Kuningan, 2019)
This study is an attempt to compare the effect of oral conferencing alongside collaborative writing on writing skills of English as a Foreign Language (EFL) learners. For this purpose, a piloted sample of the Preliminary English Test (PET) was administered to 90 intermediate female EFL learners, between 20 and 32 years old (Mage = 26). The results of this test enabled the researchers to select 60 homogenous individuals who were then randomly assigned into two experimental groups of 30 named “oral conferencing group” and “collaborative writing group”. To ensure the homogeneity among the participants in terms of their writing ability before the treatment, their scores on the writing section of the PET test were analyzed in isolation and it was considered as the pretest of the study. Oral conferencing included the discussions and negotiations among the participants and the teacher before and after writing activities followed by live teacher-student as well as student-student feedbacks. In the collaborative writing group, the participants wrote compositions in groups based on the same topics introduced in the oral conferencing group. At the end, both groups were given another piloted writing section of the PET test as the posttest. The analysis of the test scores using an independent sample t-test and analysis of covariance (ANCOVA) revealed that there is a significant difference between the effect of oral conferencing and collaborative writing on EFL learners’ writing skills. Finally, it can be concluded that EFL learners’ writing skill was more affected by applying oral conferencing rather than collaborative writing.